A 0.42-V input boost dc-dc converter with pseudo-digital pulsewidth modulation - Sun, Zhuochao (2021)
A pseudo-digital pulsewidth modulation (P-DPWM) controlled boost direct current-direct current converter is presented in this brief. By applying low-voltage analog design techniques into the traditional digital pulsewidth modulation (DPWM) structure, the proposed P-DPWM achieves new features of high resolution, low power, and small area while retaining the low-supply feature of the DPWM. A test chip has been designed and fabricated in a 65-nm CMOS process with an area of 1.44 mm2 to validate its performance. A peak efficiency of 86% is achieved. The correct functionality is also demonstrated with the controller supply as low as 0.42 V, which is ideal for sub-1 V low-supply applications.